Effect of socioeconomic and latent variables in vehicle ownership: A case study of Agartala city, India - Acharjee, Amitabha; Pratim Sarkar, Partha; Pal, Joyanta (International Journal of Engineering and Technology, 2017)
On the whole, car ownership is regarded as an imperative variable in travel behavior research. Car and motorcycle ownership are increasing rapidly in developing countries leading to an unsustainable developments. Using a data of 584 respondents from the Agartala city randomly collected, a model has been prepared to understand vehicle ownership for both car and motorized two wheeler mode (MTW). Latent variables along with socioeconomic variables such as monthly income, gender, age were used for modeling vehicle ownership using structural equation modelling. Latent variables used in this study, flexibility (Motorized Two wheeler), Negative public transportation perception and comfort (car) were found to be significant in the model. Our result suggests apart from socioeconomic variables, latent variables also explains vehicle ownership model.